Penguatan Kompetensi Digital Siswa SMA Dan SMK Melalui Pelatihan Operator Komputer Madya Di Kota Cirebon - Agus Bahtiar; Ahmad Faqih; Ainun Nisa Sari; Luthfiyyah Iffah Adelia (CV. Multi Kreasi Media, 2024)
This Community Service Program (PkM) was conducted to address the issue of insufficient digital competence among vocational and high school students in Cirebon City. The rapid advancement of digital technology requires every individual, including students, to possess adequate computer skills. A survey revealed that many students lack proficiency in basic skills such as office software usage, data processing, and computer operating systems, hindering their readiness for the workforce. Therefore, a computer operator training program was designed to enhance students' digital competence, provide them with relevant skills, and improve their competitiveness in the labor market. The program's implementation methods included theoretical and practical training, job simulations, and periodic mentoring and evaluation. The training covered fundamental materials on computer operation, office software, and computer system management. Job simulations were conducted to provide students with practical experience, while mentoring and evaluation aimed to ensure a thorough understanding of the material. The program involved coordination with partner schools, development of training modules, and preparation of necessary tools and devices. The results of this program demonstrated a significant improvement in students' digital skills. Over 80% of participants showed enhancement in office software usage, and students became more confident in using computers for academic tasks and job preparation. Partner schools also expressed interest in continuing this program sustainably. Concrete outputs from this activity included computer operator training modules, competency certificates for participants, student skill evaluation data, and partnerships with the industry for internship and employment opportunities. This program is expected to have a long-term positive impact on vocational and high school students in Cirebon City, enhance their readiness to face the challenges of the digital world, and contribute to strengthening the digital education ecosystem in the region.